Дистанционное тестирование знаний по курсу «Оптимальное стохастическое управление» - Адаменко, В. А.; Тевяшев, А. Д. (УАДО, 2004)
System of complex automated testing of knowledge gained by students has been developed. Thereto was written the program with programming language Delphi named «Test program». This program is universal and allows working with different tests, editing and running them. System of complex autotesting contains elements of current and final knowledge check-out.
Keywords: дистанционное тестирование знаний